Comparing extracellular proteins from thermostable direct haemolysin‐related haemolysin‐positive and ‐negative Vibrio parahaemolyticus strains to identify potential virulence factors. (8th January 2021) - He, Yu; Wang, Shuai; Wang, Kaiwen; Zhou, Jinwei; Han, Zhi; Pan, Zhenfen; Liu, Jingjing; He, Bin; Sun, Fengjiao; Liu, Xiao
Abstract: Vibrio parahaemolyticus, a leading foodborne pathogen that occurs naturally in estuarine and marine environments worldwide, is responsible for raising food safety issues in China. The global dissemination of this pathogen underscores the importance of understanding its virulence factors and their effects on the human host. We herein obtained and compared the secretomic profiles of the virulent ATCC17802 strain and the avirulent JHY32 strain of V. parahaemolyticus . In total, 28 extracellular proteins were identified, and most proteins that were differentially expressed in ATCC17802 were related to toxicity and environmental adaptability. In addition, various extracellular proteins with unknown function and potential virulence factors were identified. Our results provide data that can be used for the development of novel vaccines against V. parahaemolyticus .